Luther congress in Wittenberg. Issue 1 (6th March 2018) - Saarinen, Risto
Abstract: The Reformation year 2017 provided an opportunity for numerous congresses and publications. This article reports on the World Congress for Luther Research in Wittenberg. In addition to the main lectures and other significant currents of scholarship, the article also highlights some recent publications and public debates around Martin Luther's person and work.